2023
DOI: 10.1111/soc4.13101
|View full text |Cite
|
Sign up to set email alerts
|

How do you measure trust in social institutions and health professionals? A systematic review of the literature (2012–2021)

Abstract: The importance of measuring trust in health systems has been accentuated due to its correlation with important health outcomes aimed at reducing COVID‐19 transmission. A systematic review published almost a decade ago identified gaps in measures including the lack of focus on trust in systems, inconsistency regarding the dimensionality of trust and need for research to strengthen the validity of measures. Given developments in our understandings of trust since its publication, we sought to identify new scales … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The conflation of trust with related yet distinct terms is critical to the development and validation of measures, yet this consideration has been overlooked in the creation of many existing measures. For example, despite research identifying semantic distinctions between trust and confidence [ 31 , 36 ], measures continue to include confidence as a dimension of trust [ 11 ]. Further, research has demonstrated a conceptual distinction between trust and dependence, with the authors cautioning researchers who “may think they are measuring ‘trust’ and policy may be aimed at increasing ‘trust’, but unless both of them recognise the interplay between risk, familiarity and time, they may be measuring something other than trust” [ 27 ] (p. 13).…”
Section: Considerations In the Measurement Of Trustmentioning
confidence: 99%
See 4 more Smart Citations
“…The conflation of trust with related yet distinct terms is critical to the development and validation of measures, yet this consideration has been overlooked in the creation of many existing measures. For example, despite research identifying semantic distinctions between trust and confidence [ 31 , 36 ], measures continue to include confidence as a dimension of trust [ 11 ]. Further, research has demonstrated a conceptual distinction between trust and dependence, with the authors cautioning researchers who “may think they are measuring ‘trust’ and policy may be aimed at increasing ‘trust’, but unless both of them recognise the interplay between risk, familiarity and time, they may be measuring something other than trust” [ 27 ] (p. 13).…”
Section: Considerations In the Measurement Of Trustmentioning
confidence: 99%
“…This may explain why, despite the recognised multidimensionality of the construct, of the 43 measures identified in a 2013 review, 60% were unidimensional [ 39 ]. A more recent systematic review of measures of trust in social institutions, including healthcare, identified benevolence, competence, and equity as the most recurring dimensions, but the category “other” was also one of the most frequent [ 11 ]. The authors argue that the growth of the ‘other’ category is not occurring due to the rise of new dimensions to reflect the evolution of trust but rather, is an inconsistency in taxonomy.…”
Section: Considerations In the Measurement Of Trustmentioning
confidence: 99%
See 3 more Smart Citations